A high-etching-resistant yttrium-magnesium composite transparent ceramic and its preparation method and application

By using yttrium fluoride and yttrium fluoride oxide as sintering aids in ceramic materials, yttrium magnesium multiphase transparent ceramics and forming a protective fluorinated layer under plasma etching environment, the problem of easy decomposition of traditional ceramic materials in plasma etching environment is solved, and the etching resistance and density of ceramics are significantly improved.

CN119390427BActive Publication Date: 2025-04-18TONGJI UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510014128.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-18
Estimated Expiration
2045-01-06

AI Technical Summary

Technical Problem

Traditional ceramic materials are easily decomposed under plasma etching environments, resulting in wafer contamination in the equipment and affecting the quality and performance of semiconductor devices.

Method used

Yttrium fluoride (YF3) and/or yttrium oxyhydroxide (YOF) are used as sintering aids, and yttrium magnesium complex phase transparent ceramics are formed by mixing them with magnesium oxide and yttrium oxide to form a protective fluorinated layer to improve the etching resistance of the ceramics.

Benefits of technology

The etching resistance of ceramics is significantly improved, and the risk of traditional sintering additives decompose and introduce impurities under extreme conditions is avoided, ensuring high density and uniformity of ceramic materials during semiconductor manufacturing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390427B_ABST
    Figure CN119390427B_ABST
Patent Text Reader

Abstract

The present invention relates to a highly etch-resistant yttrium-magnesium composite transparent ceramic and a preparation method and application thereof. The preparation method comprises the following steps: mixing magnesium oxide and yttrium oxide in a predetermined ratio to obtain a substrate, adding yttrium-containing fluoride as a sintering aid, wherein the added mass of the yttrium-containing fluoride is 1-10% of the mass of the substrate, to form a composite ceramic body; sintering the composite ceramic body in an inert oxygen-free atmosphere to obtain the highly etch-resistant yttrium-magnesium composite transparent ceramic; the etching depth of the highly etch-resistant yttrium-magnesium composite transparent ceramic is 300-500nm / h. Compared with the prior art, the yttrium-containing fluoride is used as a sintering aid to form a stable protective fluoride layer on the ceramic surface, thereby improving the etching resistance of the ceramic and avoiding the risk of decomposition and introduction of impurities in an etching environment. The highly etch-resistant yttrium-magnesium composite transparent ceramic is particularly suitable for etching equipment in semiconductor manufacturing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of functional ceramics and relates to a highly etch-resistant yttrium-magnesium composite transparent ceramic and a preparation method and application thereof. Background Art

[0002] In the semiconductor manufacturing process, as integrated circuits develop towards smaller feature sizes, plasma etching technology plays a vital role in fine microstructure processing. However, the corrosion and sputtering of the processing materials by the high-energy ion flow in the etching environment will seriously affect the etching resistance of the inner wall of the equipment and key components, thus determining the manufacturing accuracy and yield.

[0003] Traditional ceramic materials, such as alumina (Al 2 O 3 ) and yttrium oxide (Y 2 O 3 ), due to its excellent hardness, melting point and chemical stability, it is often used in etching equipment. However, during the high-temperature sintering process, these ceramic materials need to add sintering aids to reduce the sintering temperature and improve the density. Traditional sintering aids such as calcium oxide (CaO), lithium oxide (Li 2 O), etc., are easily decomposed and release harmful reactants in a high-energy etching environment. These reactants may introduce new elemental impurities, causing contamination of the wafers in the equipment, thereby affecting the quality and performance of semiconductor devices.

[0004] In order to overcome this problem, the demand for pollution-free sintering aids has gradually increased in recent years. 3 ) is used as a sintering aid to improve the light transmittance of ceramics and reduce the sintering temperature. There is little research on its specific application in plasma etching environment. Summary of the invention

[0005] The purpose of the present invention is to provide a highly etch-resistant yttrium-magnesium composite transparent ceramic and its preparation method and application, using yttrium fluoride (YF 3 ) and / or yttrium oxyfluoride (YOF) and other fluorides as sintering aids have excellent chemical and thermal stability and can form a protective fluoride layer on the surface of ceramic materials, significantly improving the etching resistance of ceramics. 3 ) and yttrium oxyfluoride (YOF) can reduce the sintering temperature and promote the ion diffusion between particles during the sintering process, thereby optimizing the microstructure and density of the ceramic. 3 ) and / or yttrium oxyfluoride (YOF) and other fluorides as sintering aids to prepare yttrium-magnesium composite transparent ceramics, which can not only effectively enhance the etching resistance of ceramics, but also avoid the pollution problems caused by traditional sintering aids, and has broad application prospects.

[0006] The purpose of the present invention can be achieved by the following technical solutions:

[0007] The first object of the present invention is to provide a method for preparing a yttrium-magnesium composite transparent ceramic with high etching resistance, the preparation method comprising the following steps:

[0008] (a) mixing magnesium oxide and yttrium oxide in a predetermined ratio to obtain a substrate, adding yttrium-containing fluoride (YOxF) as a sintering aid, wherein the added mass of the yttrium-containing fluoride is 1-10% of the mass of the substrate, to form a composite ceramic body;

[0009] (b) sintering the composite ceramic body in an inert oxygen-free atmosphere, controlling the sintering temperature between 1400° C. and 1700° C., and holding the temperature for 1 to 4 hours to obtain the highly etch-resistant yttrium-magnesium composite transparent ceramic;

[0010] The etching depth of the highly etch-resistant yttrium-magnesium composite transparent ceramic is 300-500 nm / h.

[0011] Furthermore, the molar ratio of magnesium oxide to yttrium oxide is 4:1.

[0012] Furthermore, the inert oxygen-free atmosphere is an inert gas atmosphere (such as argon) or a nitrogen atmosphere (nitrogen containing a small amount of hydrogen). The composite ceramic body is placed in a sintering furnace and sintered in an inert oxygen-free atmosphere to avoid volatilization and decomposition of fluoride.

[0013] Furthermore, step (a) includes the following process:

[0014] Magnesium oxide and yttrium oxide are mixed in a predetermined ratio to obtain a substrate, and yttrium-containing fluoride is added as a sintering aid to obtain a mixed powder, wherein the added mass of the yttrium-containing fluoride is 1-10% of the mass of the substrate, and the mixed powder is pressed into a disc-shaped green body by a molding method at a molding pressure of 150 MPa to form a composite ceramic green body.

[0015] Furthermore, the added mass of the yttrium-containing fluoride is 3-5% of the mass of the substrate.

[0016] Further preferably, the added mass of the yttrium-containing fluoride is 5% of the mass of the substrate.

[0017] Furthermore, the sintering temperature is controlled between 1300° C. and 1700° C. A suitable sintering temperature (usually 1500-1700° C.) is used, and the heating rate and holding time are controlled to ensure high density and uniform microstructure of the final ceramic material.

[0018] Furthermore, the yttrium-containing fluoride is yttrium fluoride (YF 3 ), yttrium oxyfluoride (YOF) or more.

[0019] YF 3 And YOF as a sintering aid has the following advantages:

[0020] Lower the sintering temperature: At high temperature, YF 3 The fluorine element in YOF can reduce the surface energy of the matrix and promote the bonding between particles, which is especially suitable for YOF with high melting point. 2 O 3 -MgO composites;

[0021] Promote ion diffusion: Fluoride additives can accelerate ion diffusion during sintering, help improve the density of ceramics, optimize the microstructure, and enhance the mechanical properties of the material.

[0022] Furthermore, by 2 O 3 YF is added to the MgO matrix 3 and YOF, which can not only inhibit grain growth and obtain a fine and uniform grain structure, but also generate fine second phase particles, which helps to improve the mechanical properties of the material (such as flexural strength and fracture toughness) and further enhance the etching resistance of the ceramic.

[0023] Furthermore, the etching depth detection conditions include: using a plasma etcher, the etching environment is a plasma atmosphere SF 6 / Ar / O 2 , 550 W RF source power, 100 W bias power, 11 mTorr pressure; etching time 120 min.

[0024] The second object of the present invention is to provide a highly etch-resistant yttrium-magnesium composite transparent ceramic, the etching depth of the highly etch-resistant yttrium-magnesium composite transparent ceramic is 300-500nm / h, and the pollutant release of the highly etch-resistant yttrium-magnesium composite transparent ceramic during the etching process is less than 0.5ppm.

[0025] The third object of the present invention is to provide an application of a yttrium-magnesium multiphase transparent ceramic with high etching resistance, and to use the yttrium-magnesium multiphase transparent ceramic with high etching resistance in etching equipment in semiconductor manufacturing.

[0026] Furthermore, the ceramic material is particularly suitable for plasma etching resistant lining in semiconductor manufacturing equipment.

[0027] Furthermore, yttrium-containing fluoride is used as a sintering aid to form a stable protective fluoride layer on the ceramic surface, thereby improving the etching resistance of the ceramic and avoiding the risk of decomposition and introduction of impurities in the etching environment.

[0028] Compared with the prior art, the present invention has the following characteristics:

[0029] 1) The highly etch-resistant yttrium-magnesium composite transparent ceramic provided by the present invention is particularly suitable for etching equipment in semiconductor manufacturing. Traditional ceramic materials are prone to impurity contamination during plasma etching, while the present invention uses yttrium fluoride (YF 3 ) and / or yttrium oxyfluoride (YOF) as sintering aids, and magnesium oxide and yttrium oxide as the base material, which solves this problem. The present invention successfully prepares yttrium-magnesium composite transparent ceramics with high etching resistance, which are suitable for the high cleanliness requirements in semiconductor manufacturing equipment. The present invention suppresses grain growth and reduces the sintering temperature, so that the prepared ceramic material has a dense and uniform microstructure, and can form a stable fluorinated protective layer during plasma etching, which significantly improves the etching resistance of the material. The present invention avoids the impurity contamination problem that may be caused by the use of other sintering aids or the use of no sintering aids, ensures that the yttrium-magnesium composite ceramic material does not release pollutants during the semiconductor manufacturing process, and further improves the yield and service life of semiconductor equipment.

[0030] 2) The present invention adopts yttrium fluoride (YF 3 ) and / or yttrium oxyfluoride (YOF) as sintering aids can not only form a stable protective fluoride layer on the surface of yttrium-magnesium composite ceramics, significantly improving the etching resistance of ceramics, but also avoid the risk of traditional sintering aids decomposing and introducing impurities under extreme conditions. 3 ) and / or yttrium oxyfluoride (YOF) can effectively reduce the sintering temperature, promote ion diffusion, optimize the microstructure of ceramics, and thus improve the density and uniformity of ceramics.

[0031] 3) The highly etch-resistant yttrium-magnesium composite transparent ceramic provided by the present invention requires the addition of sintering aids to reduce the sintering temperature and improve the density of traditional etch-resistant ceramic materials during high-temperature sintering. However, traditional sintering aids (such as calcium oxide, lithium oxide, etc.) are easily decomposed in a plasma etching environment, and the released reactants may introduce new elemental impurities, thereby causing equipment contamination and affecting the wafer quality and device performance in the semiconductor manufacturing process. The present invention aims to provide a new highly etch-resistant yttrium-magnesium composite transparent ceramic. By avoiding the pollution risks brought by traditional additives, it can not only ensure that the yttrium-magnesium composite transparent ceramic has excellent density and etching resistance during high-temperature sintering, but also effectively avoid the generation of pollutants during the etching process. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 The figure is a comparison of the etching amount of common materials in the semiconductor field and the yttrium-magnesium composite ceramic of Example 1 of the present invention in 120 minutes (normalized).

[0033] Figure 2 This is a SEM image of the unetched yttrium-magnesium composite ceramic in Example 1 after surface polishing.

[0034] Figure 3 This is a SEM image of the yttrium-magnesium composite ceramic after etching and polishing in Example 1.

[0035] Figure 4 It is the junction of the etched area and the unetched area of ​​the yttrium-magnesium composite ceramic in Example 1, wherein the left side is the unetched area and the right side is the etched area.

[0036] Figure 5 Scanned by step Figure 4 Schematic diagram of the area.

[0037] Figure 6 This is a surface morphology of the etched yttrium-magnesium composite ceramic of Example 1.

[0038] Figure 7 This is an EDS analysis diagram of the elemental composition of the yttrium-magnesium composite ceramic surface of Example 1 after etching.

[0039] Figure 8 This is a mapping element distribution diagram of the etched yttrium-magnesium composite ceramic surface of Example 1.

[0040] Fig. 9 Shown is a schematic diagram of the yttrium-magnesium composite ceramic surface of Example 1 during the etching service process. DETAILED DESCRIPTION

[0041] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the accompanying drawings and the following embodiments are only used to illustrate the present invention, rather than to limit the present invention. It should be pointed out that for those of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.

[0042] Any features such as preparation methods, materials, structures or composition ratios that are not clearly described in this technical solution shall be deemed as common technical features disclosed in the prior art.

[0043] In the following embodiments, the etching conditions in the etching resistance test are as follows: ICP-601 plasma etcher is used, and the etching environment is plasma atmosphere (SF 6 / Ar / O 2 , 550 W RF source power, 100 W bias power, 11 mTorr pressure); etching time: 45 min. Contaminants during etching were detected using ICP-MS.

[0044] Example 1

[0045] This embodiment provides a highly etch-resistant yttrium-magnesium composite transparent ceramic, comprising the following steps:

[0046] 1. Raw material preparation

[0047] Weigh high purity yttrium oxide (Y 2 O 3 , purity ≥ 99.99%) and magnesium oxide (MgO, purity ≥ 99.9%) powders to ensure the high purity and good dispersibility of the raw materials.

[0048] 2. Preparation of yttrium fluoride (YF 3 )

[0049] Y 2 O 3 The powder was slowly added to a 5% hydrofluoric acid (HF) solution, the reaction temperature was controlled at 25-30°C, and the reaction time was 3 hours. 3 ) is completely formed and the safety of the reaction should be avoided. After the reaction is completed, YF 3 The precipitation was then washed with deionized water several times to remove the residual acid solution, and YF 3 The precipitate was dried at 60 °C for 8 hours to obtain pure YF 3 powder.

[0050] 3. Mixing of sintering aids

[0051] YF 3 Powder Press Y 2 O 3 5% of the total weight of the mixed powder of Y 2 O 3 In the mixed powder of Y and MgO, 2 O 3 The molar ratio of MgO is 1:4 and they are mixed thoroughly.

[0052] 4. Molding and sintering

[0053] The mixed powder was pressed into a disc-shaped body with a diameter of 10 mm and a thickness of 1 mm by a molding method. The molding pressure was 150 MPa to ensure the density of the body and obtain a composite ceramic body. The formed body was then placed in an oxygen-free atmosphere (argon) for sintering. The specific sintering procedure is as follows:

[0054] Heating rate: 10℃ / min, heating to 1500℃ (sintering temperature) and maintaining for 4 hours.

[0055] Cooling rate: 5℃ / min to room temperature, to obtain a dense and highly etch-resistant yttrium-magnesium composite transparent ceramic sample.

[0056] 5. Performance Testing

[0057] Transmittance: The transmittance test results show that the transmittance of the sample in the wavelength range of 400-700nm is an average of 75%. This transmittance indicates that the ceramic material has high transparency and is suitable for high-precision etching equipment in semiconductor manufacturing.

[0058] Microstructure: The microstructure of the samples was observed using a scanning electron microscope (SEM), and the results showed that the grains were uniform and there was no abnormal grain growth, which contributed to the mechanical properties and etching resistance of the material.

[0059] Mechanical properties: The test results show that the bending strength of the sample is 296 MPa and the fracture toughness is 2.53 MPa·m ^1 / 2 , showing excellent mechanical properties and can effectively cope with the high-load working environment in the semiconductor manufacturing process.

[0060] Crystal structure analysis: The crystal structure of the sample was analyzed by X-ray diffraction (XRD). The results showed that the main component was Y 2 O 3 -MgO composite phase, no impurity phase is generated, indicating that YF 3 As a sintering aid, it does not interfere with the basic structure of the ceramic.

[0061] As shown in Table 1, the etching resistance test: The sintered samples were tested for etching resistance. The results showed that the samples showed excellent corrosion resistance in the plasma etching environment, with an etching depth of only 300~500nm / h, which was significantly better than the samples without sintering aids. This performance verifies that YF 3 It has the function of improving the etching resistance in ceramic materials.

[0062] As shown in Table 1, contaminant detection: Contaminants in the etching process were detected. Compared with the samples without sintering aids, no newly introduced impurity elements were detected.

[0063] Example 2

[0064] This embodiment provides a highly etch-resistant yttrium-magnesium composite transparent ceramic, comprising the following steps:

[0065] 1. Raw material preparation

[0066] Prepare high purity Y 2 O 3 and MgO powder, the purity requirement is the same as that in Example 1.

[0067] 2. Preparation of yttrium oxyfluoride (YOF)

[0068] The prepared YF 3 (The preparation method is the same as in Example 1) and Y 2 O 3The mixture was uniformly mixed in a 1:1 molar ratio and calcined at 800°C for 6 hours in an inert atmosphere (argon). After cooling, the mixture was crushed to obtain YOF powder. This step ensured the high purity of YOF and its stability during the sintering process.

[0069] 3. Addition and molding of sintering aids

[0070] Press Y to remove the YOF powder. 2 O 3 5% of the total weight of the mixed powder of MgO and Y 2 O 3 and MgO mixed powder (Y 2 O 3 The mixed powder was then pressed under a pressure of 150 MPa (the pressing method was the same as in Example 1) to maintain the compactness of the green body.

[0071] 4. Sintering process

[0072] The green body was placed in a nitrogen atmosphere, heated to 1500°C and maintained for 3 hours. After sintering, the temperature was slowly lowered (5°C / min) to room temperature to prevent the sample from cracking and ensure the stability of the sample morphology, thereby obtaining a dense, highly etching-resistant yttrium-magnesium composite transparent ceramic sample.

[0073] 5. Performance Testing

[0074] Transmittance: The transmittance test results show that the transmittance of the sample in the wavelength range of 400-700nm is an average of 75%. This transmittance indicates that the ceramic material has high transparency and is suitable for high-precision etching equipment in semiconductor manufacturing.

[0075] Microstructure: The microstructure of the samples was observed using a scanning electron microscope (SEM), and the results showed that the grains were uniform and there was no abnormal grain growth, which contributed to the mechanical properties and etching resistance of the material.

[0076] Mechanical properties: The test results show that the bending strength of the sample is 315MPa and the fracture toughness is 2.78 MPa·m ^1 / 2 , showing excellent mechanical properties and can effectively cope with the high-load working environment in the semiconductor manufacturing process.

[0077] Crystal structure analysis: The crystal structure of the sample was analyzed by X-ray diffraction (XRD). The results showed that the main component was Y 2 O 3 -MgO composite phase, and no impurity phase was generated, indicating that YOF as a sintering aid did not interfere with the basic structure of the ceramic.

[0078] As shown in Table 1, the etching resistance test: The etching resistance test of the sintered samples showed that the samples showed excellent corrosion resistance in the plasma etching environment, and the etching depth was only 300~500nm / h, which was significantly better than the samples without sintering aids. This performance verifies the role of YOF in improving the etching resistance of ceramic materials.

[0079] As shown in Table 1, contaminant detection: Contaminants in the etching process were detected. Compared with the samples without sintering aids, no newly introduced impurity elements were detected.

[0080] Comparative Example 1

[0081] This comparative example provides a yttrium-magnesium composite transparent ceramic. Compared with Example 1, in this example, no sintering aid is added (i.e., no YF 3 or other sintering aids).

[0082] At the same time, the sintering temperature was adjusted to 2000°C. The change in sintering temperature was due to the fact that no sintering aid was added.

[0083] Comparative Example 2

[0084] This comparative example provides a yttrium-magnesium composite transparent ceramic. Compared with Example 1, in this example, aluminum oxide (Al 2 O 3 ) as a sintering aid (i.e. without adding YF 3 ), add the same amount according to Y 2 O 3 and MgO were added at 5% of the total weight of the mixed powder.

[0085] Comparative Example 3

[0086] This comparative example provides a yttrium-magnesium composite transparent ceramic. Compared with Example 1, in this example, additional Y 2 O 3 As a sintering aid (i.e. without adding YF 3 ), add the same amount according to Y 2 O 3 (Y in the substrate 2 O 3 ) and MgO in an amount of 5% by weight of the total weight of the mixed powder.

[0087] Comparative Example 4

[0088] This comparative example provides a yttrium-magnesium composite transparent ceramic. Compared with Example 1, in this example, YF 3 As a sintering aid, the amount added is Y 2 O 3 (Y in the substrate 2 O 3) and MgO mixed powder is added at 25% of the total weight. Compared with Example 1, the yttrium-magnesium composite transparent ceramic obtained in this comparative example has decreased etching resistance, which is due to the excessive proportion of sintering aids, which leads to an increase in ceramic grain boundary phases, limited grain growth, increased porosity, and reduced thermal stability and phase structure stability. These factors jointly weaken the mechanical strength and chemical stability of the ceramic, making it more susceptible to chemical and physical etching in a plasma environment, thereby significantly reducing the etching resistance.

[0089] Table 1 Effect of sintering aids on performance

[0090]

[0091] As shown in Table 1, the Y-Mg composite transparent ceramic without additives or using conventional Al 2 O 3 Yttrium-magnesium composite transparent ceramics as sintering aids or additional addition of Y 2 O 3 The yttrium-magnesium composite transparent ceramic has a deep etching depth and releases a large amount of pollutants during the etching process. However, the yttrium fluoride or yttrium fluoride oxide of the present application can significantly reduce the etching depth to less than 300~500nm / h due to the formation of a surface protective fluoride layer, and during the sintering process, the fluoride layer can significantly reduce the amount of pollutant release.

[0092] Figure 1 The comparison of the etching amount of the common materials in the semiconductor field and the yttrium-magnesium composite ceramic of Example 1 of the present invention in 120 minutes is shown, and the etching rate of aluminum oxide (rat=13.2um / h) is used as the reference for normalization, that is, the etching rate of aluminum oxide is 1 ( Figure 1 In the figure, Al2O3=1), the vertical axis is the magnification. Figure 1 In the figure, the magnesium-aluminum composite phase (with YF3 additive) represents the yttrium-magnesium composite ceramic prepared in Example 1. The results show that the yttrium-magnesium composite ceramic prepared in Example 1 using YOxF as a sintering additive has obvious etching advantages.

[0093] Figure 2 This is a SEM image of the unetched yttrium-magnesium composite ceramic after surface polishing. The grain boundaries are distinct, and the magnesium oxide ceramic plays a pinning effect, making the composite ceramic have uniform and relatively small grains.

[0094] Figure 3 This is the SEM image of the etched yttrium-magnesium composite ceramic after surface polishing. With the start of etching service (45 minutes measurement), a fluoride layer gradually forms on the surface. The fluoride layer and the compounds selected as the sintering aid play a combined positive role in protecting the etching and avoiding the generation of new pollution.

[0095] Figure 4It is the junction of the etched area and the unetched area of ​​the yttrium-magnesium composite ceramic in Example 1, wherein the left side is the unetched area and the right side is the etched area.

[0096] Figure 5 Scanned by step profiler (ET150, KOSAKA, Japan) Figure 4 The results show that the area is obviously raised due to the fluoride layer formed in the etched area on the right.

[0097] Figure 6 The surface morphology of the etched yttrium-magnesium composite ceramic of Example 1 is shown. After etching, uneven pits appear on the surface.

[0098] Figure 7 The EDS analysis shows the elemental composition of the surface of the yttrium-magnesium composite ceramic of Example 1 after etching, and an yttrium fluoride layer can be seen on the surface.

[0099] Figure 8 In order to map the element distribution on the etched surface of the yttrium-magnesium composite ceramic of Example 1, it can be seen that the yttrium element is evenly distributed on the surface after etching, and the fluorine element is formed in the pits formed by etching.

[0100] Fig. 9 As shown, as the service process progresses, the fluorinated layer is sputtered and the underlying ceramic surface is exposed to the gas again to carry out the cycle process.

[0101] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A method for preparing a highly etch-resistant yttrium-magnesium composite transparent ceramic, characterized in that: The preparation method comprises the following steps: (a) mixing magnesium oxide and yttrium oxide in a predetermined ratio to obtain a substrate, adding yttrium fluoride and / or yttrium oxyfluoride as a sintering aid, wherein the added mass of the yttrium fluoride and / or yttrium oxyfluoride is 1 to 10% of the mass of the substrate, to form a composite ceramic body; (b) sintering the composite ceramic body in an inert gas atmosphere or a nitrogen atmosphere, controlling the sintering temperature between 1400° C. and 1700° C., and holding the temperature for 1 to 4 hours to obtain the highly etch-resistant yttrium-magnesium composite transparent ceramic; The etching depth of the highly etch-resistant yttrium-magnesium composite transparent ceramic is 300-500 nm / h; The molar ratio of magnesium oxide to yttrium oxide is 4:1; The added mass of the yttrium fluoride and / or yttrium oxyfluoride is 5% of the mass of the substrate; The etching depth detection conditions include: A plasma etcher was used, the etching environment was a plasma atmosphere of SF6 / Ar / O2, 550 W RF source power, 100 W bias power, 11 mTorr pressure; and the etching time was 120 min.

2. The method for preparing a highly etch-resistant yttrium-magnesium composite transparent ceramic according to claim 1, characterized in that: The step (a) of forming a composite ceramic body comprises the following steps: The mixed powder was pressed into a disc-shaped green body by a molding method at a molding pressure of 150 MPa to form a composite ceramic green body.

3. A highly etching-resistant yttrium-magnesium composite transparent ceramic prepared by the preparation method as described in any one of claims 1 to 2.

4. An application of the highly etch-resistant yttrium-magnesium composite transparent ceramic as claimed in claim 3, characterized in that: The highly etching-resistant yttrium-magnesium composite transparent ceramic is used in etching equipment in semiconductor manufacturing.

5. The use of a highly etch-resistant yttrium-magnesium composite transparent ceramic according to claim 4, characterized in that: Yttrium fluoride and / or yttrium fluoride oxide are used as sintering aids to form a stable protective fluoride layer on the ceramic surface, thereby improving the etching resistance of the ceramic and avoiding the risk of decomposition and introduction of impurities in the etching environment.

Citation Information

Patent Citations

  • Application method of oxide transparent ceramic material sintering aid

    CN115010503A